Feeling good - bodies in destination brand love - Aro, Kaisa; Tähtinen, Jaana (Elsevier, 2025)
This study extends the conceptualization of destination brand love with a bodily dimension. Although tourism research and affective and cognitive science acknowledge that we sense the world through our bodies, the human body seldom appears in brand-love studies. This study shifts the focus from the antecedents and consequences of brand love to consumers' multidimensional brand-love relationships. We distinguish two ontological approaches to brand love by studying an outdoor destination brand. The first conceptualizes destination brand love as a four-dimensional entity of bodily, cognitive, emotional, and behavioral dimensions. The second is a processual conceptualization considering destination brand-loving as an ongoing process. The study offers two alternative and connected conceptualizations for tourism marketing scholars: destination brand love and destination brand-loving.